Inhibition Biosensor Based on DC and AC Electrical Measurements of Bacteria Samples. (2017) - Abu-Ali, H.; Nabok, A.; Smith, T.; Al-Shanawa, M.
Abstract: The main idea of this project is to utilise microorganisms (bacteria) as sensing elements in the inhibition type biosensors for detection of heavy metals and pesticides which are dissolved in water. This work focuses on developing novel, cost-effective sensing technologies for detection of environmental pollutions. Two types of bacteria ( E. coli and S. oneidensis ) which are inhibited by heavy metals were used in this work. The bacteria density or concentration was characterised first with optical techniques of fluorescence microscopy, optical density OD600, and flow cytometry. Then a series of electrochemical measurements were carried out on the same bacteria samples. The study of the effect of heavy metals on the above bacteria revealed a possibility of pattern recognition of the above pollutants.